Analysis of Student Constraints in Entrepreneurship through the Analytical Hierarchy Process (AHP) Approach - Sutarmin Sutarmin (Universitas Proklamasi 45, 2023)
To increase the number of entrepreneurs in Indonesia, Peradaban University began to change the patterns of education, so the students not only have high scores in academics but they also have entrepreneurial skills. Despite this subject, entry of students into the field of entrepreneurship has always been faced with many barriers and most of them have not been able to analyze the barriers. This study uses a mixed method of quantitative and qualitative methods. Analytical Hierarchy Process (AHP) was used to analyze the dominant factors of the barriers. While the interview method was used as a qualitative method to find out the solution to the barriers. Respondents in this study were students at Peradaban University that have been entrepreneurs for at least one month. Data were obtained by spreading questionnaires to 32 students and interviewing four students. The result of the analysis shows that the dominant factors are environment of campus barriers (25.79%) followed by financial barriers (24.84%), character barriers (18.48%), educational barriers (17.03%) and family barriers (13.85%). And some solutions provided are learning time management, making the priority scale, approaching the lecturer, looking for investors, and inviting other friends to run the business together.